PRODUCTIVITY EVALUATION OF RICE PROMISING LINES IN ORANSBARI DISTRICT, MANOKWARI REGENCY - Fransiska Renita Anon Basundari; Abdul Wahid Rauf (Widyariset, 2013)
Currently, the average of rice productivity in Manokwari only reached 4.3 ton ha-1. The rice varieties commonly planted in Manokwari are Ciherang, Mekongga, and Cigeulis, with the average productivity for each variety 3.87 ton ha-1, 4.01 t ha-1, and 4.11 t ha-1. The objective of the experiment was to obtain promising lines of rice which have high productivity (higher than 20%) of the current situation in Manokwari. The research was conducted in the District of Oransbari, Manokwari, West Papua in February until November 2010. It was arranged in Randomized Block Design, using four promising lines (RUTTST96B-15-1-2-2-2-1, BPT164C-68-7-3-2, RUTTSG-69-1B-1-1-3-2-1, IR71146-122-1-1-2) and four varieties of rice (Ciherang, IR64, Tukad Unda, and Memberamo) as a treatment, with three replications. The parameters observed include plant height, panicle number/clump, panicle length, yield, and the amount of filled grain. From the analysis, there were two promising lines namely BPT164C-68-7-3-2 and RUTTSG-96B-15-1-2-2-2-1. It showed the increasing of productivity about 36.27% and 52.09% from the current situation in Manokwari, and might be evaluated to be further developed in Oransbari District, Manokwari Regency.